1976
DOI: 10.1002/pol.1976.180140305
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of poly(m‐phenylene isophthalamide)

Abstract: The crystal structure of poly(m‐phenyulene isophthalamide) was determined by x‐ray analysis. The triclinic cell, with a = 5.27 Å, b = 5.25 Å, c (fiber axis) = 11.3 Å, α = 111.5°, β = 111.4° and γ = 88.0° and space group P1, contains one monomeric unit. The crystal density is 1.47 g/cc. The molecules in the crystal are contracted by 1 Å per monomeric unit from the fully extended conformation, and the planes of the benzene rings and adjacent amide groups make angles of about 30°. The crystal is composed of molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 6 publications
1
42
2
Order By: Relevance
“…Its amine functional group is situated with the meta orientation on the phenyl ring in a monomer unit, as opposed to the para configuration in Kevlar. This small difference in molecular structure changes the optimal bond angles of phenyl-nitrogen and phenyl-carbon bonds in Nomex, resulting in a "crumpled" chain structure that cannot crystallize into stacked sheets [7]. This causes it to take on a "jungle gym" structure [7], with randomly stacked polymer chains, and a resulting lower overall crystallinity than Kevlar [7].…”
Section: Continuous Dynamic Analysis Of Kevlar and Nomexmentioning
confidence: 99%
See 1 more Smart Citation
“…Its amine functional group is situated with the meta orientation on the phenyl ring in a monomer unit, as opposed to the para configuration in Kevlar. This small difference in molecular structure changes the optimal bond angles of phenyl-nitrogen and phenyl-carbon bonds in Nomex, resulting in a "crumpled" chain structure that cannot crystallize into stacked sheets [7]. This causes it to take on a "jungle gym" structure [7], with randomly stacked polymer chains, and a resulting lower overall crystallinity than Kevlar [7].…”
Section: Continuous Dynamic Analysis Of Kevlar and Nomexmentioning
confidence: 99%
“…In this regime, as above, chains begin to unravel, increasing structural disorder. Regime II begins after the loss factor reaches a maximum, and the "jungle gym" [7] structure in Nomex begins to align with the tensile axis. As above, a very slight leveling-off of the loss factor decrease is observed with increasing strain in this regime, due to molecular-level chain alignment reaching a maximum.…”
Section: Continuous Dynamic Analysis Of Kevlar and Nomexmentioning
confidence: 99%
“…It has been reported that highly crystalline poly(1,4-phenylene isophthalate) were obtained as precipitated plate-like crystals by the reaction-induced crystallization during the polymerization of isophthalic acid and PPDA. 22 The PPHIA hollow spheres were formed via the liquid-liquid phase separation. The PPHIA hollow spheres possessed high crystallinity, nevertheless the liquid-liquid phase separation mode, bulky OH substituent and the irregular cross-linking structure ought to lower the crystallinity.…”
Section: Resultsmentioning
confidence: 99%
“…In a word, membranes which were prepared by first blending GO in the polymer dopes and then undergoing phase inversion protocol exhibited higher water flux and improved antifouling properties. Poly (m-phenylene isophthalamide) (PMIA) has great thermal resistivity (T g 270 • C), good chemical stability, elongation at break and toughness as well as high mechanical strength, which explains PMIA is an outstanding membrane material [38][39][40]. Wang et al fabricated a PMIA hollow fiber NF membrane that could effectively remove a persistent organic pollutant, perfluorooctane sulfonate (PFOS), from water [41].…”
Section: Introductionmentioning
confidence: 99%